Modern quantum mechanics - Sakurai, J. J. ([S.l.] : Addison Wesley, 1993)
This best-selling classic sets the standard for the quantum mechanics physics market. It provides a graduate-level, non-historical, modern introduction of quantum mechanical concepts for first year graduate students. The author was a noted theorist in particle theory, and was well renowned in his area of expertise. This revised edition retains the original material, but adds topics that extend its usefulness into the 21st century. Students will still find such classic developments as neutron interferometer experiments, Feyman path integrals, correlation measurements, and Bell's inequality. Updated material includes time independent perturbation theory for The Degenerate Case which can be found in 5. New supplementary material is at the end of the text.